การสื่อสารระหว่างบุคคลในการสนับสนุนให้เกิดการทำประกันชีวิต - วารุณี สุวรรณาพิสิทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The purpose of this research was to study interpersonal communication between life insurance agents and insurees, that is, communication process as well as the persuasive strategies including studying in perception, attitude and behavior of insurees. The sample groups for this research are 20 life insurance agents who represented of 10 life insurance companies and 40 insurees which were customers of the sampled life insurance agents. The research methodology comprised depth interview and content analysis. The results of this research are as follows : 1. The communication process between life insurance agents and insurees began with open-up step by approaching the customers through having a good relationship. Then life insurance agents proposed life insurance to the insurees. That was selling step. The final step was closing the case by making insurees buy life insurance. The content of messages which life insurance agents used were 6 types divided by the objectives for buying life insurance; for education,business s protection, disability, debt, investment and medical cares. 2. The persuasive strategies of life insurance agents that made insurees buy life insurance was compliance-gaining strategies, which were in concordance with the persuasive strategies which insurees thought life insurance agents used seven persuasive strategies from all 16 strategies were perceived as being similar : expertise (negative), aversive stimulation, debt, moral appeal, self-feeling (positive), altercasting (positive) and altercasting (negative). 3. The insurees perception in purchasing life insurance was having good benefit for themselves and their families. When something happened, life insurance was valuable and this created positive attitude of insurees towards life insurance. Also trustworthiness of life insurance agents made buying life insurance a good financial planning. The negative attitude of insurees was, however, that life insurance agents very often did not take good care of insurees.